Epilepsy Outcome in Periventricular Nodular Heterotopia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The clinical, electroencephalographic, and neuroimaging features and course of seizures in 16 patients with periventricular (subependymal) nodular heterotopia (PNH) were investigated at the University of Bologna, Italy.